Physicochemical Characteristics and Lactic Acid Bacterial Diversity of an Ethnic Rice Fermented Mild Alcoholic Beverage, Haria - Ghosh, Kuntal; Adak, Atanu; Halder, Suman K.; Mondal, Keshab C. (Frontiers in Sustainable Food Systems, 2021)
Haria, a rice fermented alcoholic beverage, is prepared and consumed by the vast number of Indian tribal people as a staple drink. Lactic acid bacteria are the dominant microbial community in this beverage. Participating lactic acid bacterial diversity in this beverage were determined by using PCR denaturing gradient gel electrophoresis (PCR-DGGE) as Lactobacillus plantarum, Lactobacillus brevis, Lysinibacillus sp., Lysinibacillus fusiformis, and a group of uncultured Bacillus sp. The beverage was enriched with a significant amount of lactic acid (17.63 mg/g), acetic acid (0.18 mg/g), folic acid, thiamine, pyridoxine, ascorbic acid, linolenic acid, linoleic acid, palmitic acid, and oleic acid. The phytase activity in this beverage was shown highest (18.93 U/g) at the fourth day of fermentation. The beverage was also augmented with essential minerals like calcium, ferrous, magnesium, and sodium, whereas the quantity of chromium, lead, cobalt, and nickel were gradually decreased during the course of fermentation. Gas chromatography–mass spectrometry (GC-MS) analysis clearly revealed that three types of esters were produced during fermentation. This study clearly demonstrated that a group of lactic acid bacteria along with other microorganism provide a wide array of bioactive substances make this beverage more nutritious.